Tongluo Xingnao Effervescent Tablet preserves mitochondrial energy metabolism and attenuates cognition deficits in APPswe/PS1De9 mice. (6th September 2016) - Dai, Yuan; Ma, Tao; Ren, Xiangyi; Wei, Jiangping; Fu, Wenjun; Ma, Yuntong; Xu, Shijun; Zhang, Zhanjun
Graphical abstract: Highlights: TXET, a traditional Chinese herbal formula, has been widely used for decades in China. TXET can ameliorate cognitive dysfunction. We investigated the effects of TXET on mitochondrial function and energy metabolism in APPswe/PS1De9 mice. TXET increased the mitochondrial membrane potential, energy charge levels, activity of respiratory chain complexes and Na+-K+ ATPase activity in APPswe/PS1De9 mice. Abstract: Tongluo Xingnao Effervescent Tablet (TXET), a traditional Chinese herbal formula composed of Ligusticum chuanxiong hor, Scutellaria baicalensis Georgi and Angelica sinensis, has been widely used to treat Alzheimer's disease (AD) and related dementias for decades in China. In the present study, we investigated the effects of TXET on mitochondrial function, energy metabolism and cognitive amelioration in the APPswe/PS1De9 transgenetic mouse model of AD. The energy charge and phosphocreatine, activity of the mitochondrial electron transport chain complexes, mitochondrial membrane potential, activity of Na + -K + ATPase and the expression levels of Bcl-2 and Bax in the brains were measured, respectively. TXET exhibits significant protection on mitochondrial function and energy supply in addition to ameliorating cognitive decline in APPswe/PS1De9 mice. TXET rescues mitochondrial function by increasing the mitochondrial membrane potential, energy charge levels, activity of respiratory chain complexes and Na + -K + ATPase activity. These findings suggest that TXET may attenuate cognition impairment through the restoration of mitochondrial function and energy metabolism in the brains in APPswe/PS1De9 mice.